2021
DOI: 10.1016/j.celrep.2021.108787
|View full text |Cite
|
Sign up to set email alerts
|

Proteogenomics of glioblastoma associates molecular patterns with survival

Abstract: Highlights d Integrating proteomics and transcriptomics to study survival in GBM patients d Proteomics-based classification identifies three subtypes d Correlation analysis reveals survival patterns unique to the protein level d Incorporating single-cell published data associates subpopulations with survival

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 78 publications
4
28
0
Order By: Relevance
“…We then assessed at the individual gene level Spearman correlations between RNA and protein expression levels in seven human cancer types. We obtained 0.17 mean Spearman correlation that varied from 0.017 for Hepatocellular Carcinoma till 0.27 for Lung Adenocarcinoma samples ( Figure 2 ), which is in line with the previous results, i.e., ~0.16–0.35 correlation between the RNA- and proteome-based gene expression levels [ 6 , 7 ].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We then assessed at the individual gene level Spearman correlations between RNA and protein expression levels in seven human cancer types. We obtained 0.17 mean Spearman correlation that varied from 0.017 for Hepatocellular Carcinoma till 0.27 for Lung Adenocarcinoma samples ( Figure 2 ), which is in line with the previous results, i.e., ~0.16–0.35 correlation between the RNA- and proteome-based gene expression levels [ 6 , 7 ].…”
Section: Resultssupporting
confidence: 91%
“…At the gene level, the correlations observed were congruent with the literature data (e.g., we observed ~0.23–0.24 correlations for ovarian cancer at the gene level, compared to ~0.3 in the previous report [ 7 ], or ~0.24–0.29 for glioblastoma in this study compared to previously observed ~0.15 [ 6 ]).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…More recently, integrated pharmaco-proteogenomic studies were performed on GBM resulting in two subgroups within the IDH wild-type group showing different prognostic and therapeutic opportunities ( Oh et al, 2020 ). Moreover, the integrative analysis of the protein profile, the RNA expression, and the patient clinical information enable the identification of specific signaling pathways related to immune, metabolic, and developmental processes and associated with a patient survival ( Yanovich-Arad et al, 2021 ). Recently, subclassification of GBM using MALDI mass spectrometry imaging associated with spatially resolved proteomics and patient survival has established the presence of three GBM subtypes corresponding to antiviral immune response, neurogenesis processes, and immune infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…Primary GBM stem cells (GSCs) have shown to reflect the diversity of GBM, recapitulate the tumour subtypes at mRNA level, and represent a good model to study the molecular profile of this cancer and explore new therapeutic targets (Johansson et al, 2020). Many efforts were undertaken to uncover gene expression signatures that are pivotal for GSC functions, expanding our understanding of the transcriptome and proteome of GBM and GSCs (Asif et al, 2019; Guardia et al, 2020; Johansson et al, 2020; Kozuka-Hata et al, 2012; MacLeod et al, 2019; Marziali et al, 2016; Mostovenko et al, 2018; Rheinbay et al, 2013; Song et al, 2017; Yanovich-Arad et al, 2021). Single-cell RNA-sequencing (scRNAseq) studies have demonstrated that GSCs are plastic and can switch between different subtypes 8 .…”
Section: Introductionmentioning
confidence: 99%